Remembering to Remember Shę́h Niyohgwaihó’dę (Our Original Instructions): A Self-Study on Indigenous Languages Programming in Six Nations - Henry, Bobby (Stanley) R. (2020)
This research portfolio investigates one aspect of the Indigenous language revitalization/reclamation movement, which is Indigenous communities’ and peoples’ reclamation over their formal education systems with hopes of preventing further loss and decline in the intergenerational transmission of Indigenous languages. More specifically, this research portfolio is a self-study that documents the longitudinal impacts of my own educational experiences in Hodinohsyó:ni language education programs, specific to the Six Nations of the Grand River Territory community. This research portfolio is compartmentalized into three tasks: 1) a literature review on Indigenous language reclamation; 2) a collection of first-hand educational experiences interwoven with Tadoda:ho’s story of self-transformation, which aligns with Indigenous storywork and storytelling; and, 3) reflexive recommendations that elementary, secondary schools, and/or communities could consider implementing for program improvement, modification or development. The main purpose for this project is to uncover the preservation of Indigenous languages aids with healing from the long-term impacts of colonial education, fosters Indigenous resurgence and Indigenous self-determination, and promotes spaces that supports building Indigenous cultural identity.